2016
DOI: 10.4103/1687-8426.184363
|View full text |Cite
|
Sign up to set email alerts
|

Role of ultrasound in assessment of diaphragmatic function in chronic obstructive pulmonary disease patients during weaning from mechanical ventilation

Abstract: ObjectivesThe aim of the study was to investigate the role of ultrasound in the evaluation of movement of the diaphragm and its value in predicting successful extubation in mechanically ventilated chronic obstructive pulmonary disease (COPD) patients in relation to other weaning parameters. Patients and methodsThe present study was conducted on 50 patients in the respiratory ICU and the Chest Department of Ain Shams University Hospitals. Patients were divided into two groups: group A and group B. Group A consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…By applying diaphragmatic US to those patients during SBT, authors found that during infancy period the measured DTF, diaphragmatic excursion and the total lung score showed highly significant correlations with weaning outcome (p < 0.001). These results were matched with results of several studies [16][17][18][19].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…By applying diaphragmatic US to those patients during SBT, authors found that during infancy period the measured DTF, diaphragmatic excursion and the total lung score showed highly significant correlations with weaning outcome (p < 0.001). These results were matched with results of several studies [16][17][18][19].…”
Section: Discussionsupporting
confidence: 90%
“…This agrees with results of other studies which reported that the cut-off value of Diaphragmatic E in the assessment of the weaning outcome is 10-11 mm with different degrees of sensitivity and specificity. Saeed et al [16] stated that it has 86.4% sensitivity and 87.5% specificity while Baess et al stated that it has 69.5% sensitivity and 71.4% specificity [14].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 24 articles were excluded for the following reasons: ten studies were not primary studies, five studies evaluated diaphragm muscle atrophy, two studies used phrenic nerve stimulation rather than ultrasonography, two studies only reported ultrasonography examination reproducibility, one study evaluated patients under MV, one evaluated only patients with high risk of reintubation and three studies were conducted on children or non-mechanically ventilated patients. Therefore, 19 studies were evaluated in the final analysis [15,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Included studies' quality assessed by the QUADAS II tool are shown in Table 1.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…DE was assessed in 701 patients enrolled in eleven studies [15,25,26,[30][31][32][33][34][36][37][38] during spontaneous breathing. The pooled sensitivity and specificity were 79.9% (I 2 = 65.3%) and 69% (I 2 = 75.1%), respectively, with DOR of 9.1 (I 2 = 59.1%).…”
Section: Diaphragmatic Excursion (De)mentioning
confidence: 99%
“…Of these, 46 were included (Figure 1). [3,5,8,11,13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Some of these 46 articles evaluated more than one diagnostic test, therefore the final analysis included evaluation data from 60 separate studies on a total of 1. Of the 60 studies, 23 evaluated respiratory muscle strength using diaphragm ultrasound (1390 patients), [3, 13, 15-18, 24, 26-28, 36-48] 6 used transdiaphragmatic twitch pressure (292 patients) [3,5,11,13,49,50] and 13 used MIP (709 patients) [3, 15-17, 25-28, 51-55].…”
Section: Characteristics Of the Studies Included In The Systematic Reviewmentioning
confidence: 99%